The Assessment of Atmospheric Pollution using Satellite Remote Sensing Technology in Large Cities in the Vicinity of Airports - Clayton, Chris R I; Retalis, Adrianos; Hadjimitsis, Diofantos G. (My University, 2002)
This paper investigates the potential of usingsatellite remotely sensed imagery for assessing atmosphericpollution. A novel approach, which comprised radiativetransfer calculations and pseudo-invariant targets fordetermining aerosol optical thickness has been developed.The key parameter for assessing atmospheric pollution inphotochemical air pollution studies is the aerosol opticalthickness. The need for identifying suitable pseudo-invariantobjects in satellite images of urban areas is of great interest for increasing the potential of earthobservation for monitoring air pollution in such areas. Theidentification of large water bodies and concrete apronsthat can serve as suitable dark and bright targetsrespectively in different geographical areas wasdemonstrated in this study. This study added evidence onthe correlation found between the visibility valuesmeasured at Heathrow Airport area during satellite overpassand aerosol optical thickness derived from Landsat-5 TMband 1 images.
Keywords: Remote sensing; Invariant targets; Pseudo; Eutrophic waters; Dark targets; Bright targets; Atmospheric pollution; Aerosol optical thickness